2010
DOI: 10.5251/abjna.2010.1.5.1061.1068
|View full text |Cite
|
Sign up to set email alerts
|

Increasing imazapyr-resistant maize yield by increasing plant density under natural Striga hermonthica infestation

Abstract: Maize (Zea mays L.) is one of the most important crops in East Africa serving both as a staple food and cash crop to millions of people. As a vegetable, it is produced as green maize cobs, sweet corn or baby corn. Yields under farmers' conditions in the Lake Victoria Basin average 1.3 t ha -1 which is less than 25% of the potential yield. This is attributed to several factors; the greatest being Striga (Striga hermonthica) which is a parasitic weed attacking several crops in the grass family. A medium term tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Chlorsulfron affects the striga attachment negatively to the host and it indicates application of 15g ha -1 of chlorsulfron with Deber variety it increases the yield by 43.84% over the control chlorsulfron with Wediaker. This result agrees with [10] who reported that treated IR-maize and increasing plant population increases the yield under natural striga infestation. It also agrees with [11] tested chlorsulfuron formulation significantly increased sorghum grain yield.…”
Section: Grain Yieldsupporting
confidence: 93%
“…Chlorsulfron affects the striga attachment negatively to the host and it indicates application of 15g ha -1 of chlorsulfron with Deber variety it increases the yield by 43.84% over the control chlorsulfron with Wediaker. This result agrees with [10] who reported that treated IR-maize and increasing plant population increases the yield under natural striga infestation. It also agrees with [11] tested chlorsulfuron formulation significantly increased sorghum grain yield.…”
Section: Grain Yieldsupporting
confidence: 93%
“…Other methods for Striga control include biological control using herbicide‐resistant maize variety (Imazapyr treatment), development of Striga‐resistant germplasm, use of fungus Fusarium isolation by applying strigolactones (Kanampiu et al., 2002; Ejeta, 2007; Illa et al., 2010; Nzioki et al., 2016; Uraguchi et al., 2018; Zwanenburg, & Blanco‐Ania, 2018; Kountche et al., 2019). All these approaches have been used with some degree of success to minimize the effect of Striga in maize production.…”
Section: Economic Impact Of Striga Infestation On Maize Production and Biology Of Striga Sppmentioning
confidence: 99%